The role of solvent-ligated metal(II) complexes incorporating (fluoroalkoxy)aluminates as weakly coordinating anions in isobutylene polymerization - Yeong, Hui Yee; Li, Yang; Kuehn, Fritz E.; Voit, Brigitte (Journal of Polymer Science Part A-Polymer Chemistry, 2013)
Nitrile-ligated copper(II) and zinc(II) complexes comprising (fluoroalkoxy)aluminates as weakly coordinating anions (WCAs) have been synthesized and applied for the polymerization of isobutylene at room temperature (30°C). The polymers obtained are in the low and moderate molecular weight range and show characteristics of the highly reactive polyisobutylene. Results indicate that the fluoroalkoxy aluminate WCAs have even a higher tolerance toward water in IB polymerization than the earlier tested perfluoroborate WCAs. Studies showed that water plays an important role in the polymerization process, which indicates a polymerization mechanism similar to a proton-initiated carbocation polymerization. The role of the WCAs and their importance for the room-temperature polymerization process was re-examined, and the effect of the addition of proton and electron donors including proton traps (2,6-di-tert-butyl-4-methylpyridine or DTBP) was studied in detail. The polymerization reaction seems to be dominated by transfer reactions that lead to the high content of exo double bonds while propagation proceeds via conventional cationic polymerization. © 2012 Wiley Periodicals, Inc.
CRIS-Team Scopus Importer:2023-03-20
Keywords: cationic polymerization; polyisobutylene; polymerization; polyolefins; transition metal chemistry; weakly coordinating anions